Tourism Knowledge and Beautiful Touristic Destinations - Poziljanov Xumoyunmirzo Gayratjon ugli; Asadullayeva Visola Bekhzod kizi (Research Parks Publishers, 2021)
In this article I have described main understanding of the Tourism and additionally several primary areas which are consisted of Tourism. Moscow, Southampton, Victoria´s Buchan Caves were written to be the touristic cities of the world. Although these places are not well-known like the Athens, Rome, Paris, Madrid I found their landscapes in my scientific work.